Lithium for Post-Electroconvulsive Therapy Depressive Relapse Prevention. Issue 2 (June 2015) - Rasmussen, Keith G.
<x xml:space="preserve">Abstract</x> Abstract Lithium has been used for several decades as a prophylactic against depressive relapse after successful index electroconvulsive therapy (ECT). The literature on this topic is reviewed, and it is concluded that, in the main, there is strong evidence that lithium can help prevent relapses in the first 6 months after index ECT. However, there are several unanswered questions about its use post-ECT, including optimal target blood level, duration of use, and concomitant antidepressant choice. In this report, the author provides a review of the evidence for using lithium in this setting, outlines the pertinent unanswered questions, and proposes future research directions and guidelines for current clinical care.